1997
DOI: 10.1074/jbc.272.13.8179
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone-dependent Gene Expression Program for Xenopus Neural Development

Abstract: Although thyroid hormone (TH) plays a significant role in vertebrate neural development, the molecular basis of TH action on the brain is poorly understood. Using polymerase chain reaction-based subtractive hybridization we isolated 34 cDNAs for TH-regulated genes in the diencephalon of Xenopus tadpoles. Northern blots verified that the mRNAs are regulated by TH and are expressed during metamorphosis. Kinetic analyses showed that most of the genes are up-regulated by TH within 4 -8 h and 13 are regulated by TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 77 publications
5
73
0
Order By: Relevance
“…Metamorphosis in Xenopus laevis is characterized by a non-functional thyroid gland in embryos, which is converted into a functional (thyroid hormonesecreting) organ during larval development -a classical T3-dependent differentiation model (Shi et al 1996, Berry et al 1998. Among the differentially T3-regulated genes during metamorphosis, Shi and co-workers described a biphasic expression pattern for the neural-specific tubulin subunit in Xenopus (Denver et al 1997) and, noteworthy, we identified a highly similar biphasic expression pattern for an -tubulin isoform in rat liver (cluster 6, Table 1, No. 59).…”
Section: Discussionmentioning
confidence: 99%
“…Metamorphosis in Xenopus laevis is characterized by a non-functional thyroid gland in embryos, which is converted into a functional (thyroid hormonesecreting) organ during larval development -a classical T3-dependent differentiation model (Shi et al 1996, Berry et al 1998. Among the differentially T3-regulated genes during metamorphosis, Shi and co-workers described a biphasic expression pattern for the neural-specific tubulin subunit in Xenopus (Denver et al 1997) and, noteworthy, we identified a highly similar biphasic expression pattern for an -tubulin isoform in rat liver (cluster 6, Table 1, No. 59).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, direct TH action on neuronal differentiation genes may be responsible for at least some of the known effects of TH on amphibian neuronal development such as its promotion of cytodifferentiation in the lateral motor column (Beaudoin, 1956;Race, 1961;Reynolds, 1963;Hughes, 1966;Decker, 1976) and other parts of the nervous system (reviewed in Kollros, 1981;Denver, 1998). However, it is currently unknown, which THresponsive genes are instrumental in mediating these effects in amphibians, even though several neuronspecific TH-responsive genes (Denver et al, 1997;Denver, 1998) Tsai and O'Malley, 1994;Shi et al, 1996Shi et al, , 1998Tata, 1996;Zhang and Lazar, 2000;Wu and Koenig, 2000). Effective DNA binding requires dimerization with other nuclear receptors, preferrably retinoid X receptors (RXR; reviewed in Zhang and Pfahl, 1993;Shi et al, 1996Shi et al, , 1998Tata, 1996;Zhang and Lazar, 2000;Wu and Koenig, 2000).…”
Section: Thyroid Hormones Promote Neurogenesis In the Spinal Cordmentioning
confidence: 99%
“…1). Thyroid hormones (TH) in amphibians are known to be sufficient and in some cases necessary for promoting proliferation of neuronal precursors (Tusques, 1949;Baffoni, 1957;Reynolds, 1966;Kaltenbach and Hobbs, 1972;Pollack and Towbin, 1975;Beach and Jacobson, 1979;Kollros, 1981;Goldberg and Pollack, 1989;Clorfene and Pollack, 1994;Marsh-Armstrong et al, 1999;Schreiber et al, 2001) and neuronal differentiation (Beaudoin, 1956;Race, 1961;Reynolds, 1963;Hughes, 1966;Decker, 1976;Kollros, 1981;Hauser and Gona, 1984;Kollros and Bovbjerg, 1990;Denver et al, 1997;Denver, 1998;Marsh-Armstrong et al, 1999). As these effects of THs are thought to be mediated by TH recep- Nieuwkoop and Faber, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Brain tissue from stage 55 tadpoles sampled on study day 8 was used for these analyses to prevent possible confounding effects of stage-dependent differences in gene expression. In brain of PER-and ETU-treated tadpoles, significantly lower mRNA expression was detected for A c c e p t e d M a n u s c r i p t 7 several genes known to be up-regulated by TH (Das et al, 2006;Denver et al, 1997) including thrb (thyroid hormone receptor ), bteb1-A (basic transcription element-binding protein 1), pcna, mcm2, and kif2C (Fig. 2).…”
Section: Treatment With Per and Etu Alters Gene Expression In Tadpolementioning
confidence: 99%